Dasuram's script : new writing from Odisha - Jenā, Monālisā; Jenā, Monālisā (Harper Perennial, 2013)
The coward / Sahadeva Sahoo -- Dasuram's script / Bhima Prusty -- The adventure of a little kau fish / Rajani Kant Mohanty -- The shiora tree / Debabrata Madanray -- Goddess of kara dongri / Yashodhara Mishra -- A new year / Devdas Chhotray -- That house / Gaurahari Das -- The sin / Paresh Patnaik -- The chemistry / Paramita Satapathy -- This short story should not be remembered / Manoj Kumar Panda -- A pitcher full of fish / Chirashree Indrasingh -- The genius / Tarun Kanti Mishra -- The shy bride / Krupa Sagar Sahoo -- Salvation / Debasis Panigrahi -- Sephania's ghastly makar / Dipti Ranjan Pattanaik -- Fourteenth February / Mona Lisa Jena